2001
DOI: 10.1046/j.1523-1755.2001.059002702.x
|View full text |Cite
|
Sign up to set email alerts
|

Progression of diabetic nephropathy

Abstract: The prognosis of diabetic nephropathy has improved during the past decades, predominantly because of effective antihypertensive treatment. Genuine normotensive patients have a slow progression of nephropathy. Several modifiable variables have been identified as progression promoters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
190
3
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(209 citation statements)
references
References 50 publications
15
190
3
1
Order By: Relevance
“…Variations in the rate of GFR decline in patients with type 2 diabetes with nephropathy have been described before in previous studies, ranging from 0.36 mL/min/1.73m 2 /year among the Japanese population11 to 4.7 mL/min/1.73m 2 /year among Brazilian subjects 19. Several other studies have also suggested an annual decline in GFR within this range 12131828. In our study, we showed an average of 3.3 mL/year drop in GFR and even greater among patients who reached ESRD (5.9 mL/year).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Variations in the rate of GFR decline in patients with type 2 diabetes with nephropathy have been described before in previous studies, ranging from 0.36 mL/min/1.73m 2 /year among the Japanese population11 to 4.7 mL/min/1.73m 2 /year among Brazilian subjects 19. Several other studies have also suggested an annual decline in GFR within this range 12131828. In our study, we showed an average of 3.3 mL/year drop in GFR and even greater among patients who reached ESRD (5.9 mL/year).…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have identified age,1617 male gender,17 lower initial glomerular filtration rate (GFR),1418 first–hospital-visit fasting plasma glucose18 and concomitant presence of retinopathy1920 as important risk factors for GFR decline. The proteinuria itself is a major risk factor for progression of DN 12151920. Above all, these risk factors for progression of chronic kidney disease (CKD) in type 2 diabetes mellitus have not been fully elucidated.…”
mentioning
confidence: 99%
“…Two decades ago, it was demonstrated that antihypertensive treatment could delay the development of end-stage renal failure by reducing the rate of decline of the GFR [21,22], a finding that has subsequently been confirmed in randomised controlled trials (see below). Observational studies indicate a decline in the GFR of 3.7 ml min −1 year −1 in patients on antihypertensive therapy [23]. Poor glucose control and hypercholesterolaemia have also been associated with a more rapid deterioration of kidney function in observational, but not interventional, studies [23,24].…”
Section: The Changing Course Of Diabetic Kidney Diseasementioning
confidence: 99%
“…Observational studies indicate a decline in the GFR of 3.7 ml min −1 year −1 in patients on antihypertensive therapy [23]. Poor glucose control and hypercholesterolaemia have also been associated with a more rapid deterioration of kidney function in observational, but not interventional, studies [23,24].…”
Section: The Changing Course Of Diabetic Kidney Diseasementioning
confidence: 99%
“…The renoprotective role of ACEI, beyond what can be attributed to BP reduction, has been shown in only 2 of 5 studies that compared these drugs to either CT or to CCB (25)(26)(27)(28)(29) in type 1 diabetic patients with overt nephropathy. In type 2 diabetic patients who also have overt nephropathy, 4 of 5 small trials that evaluated the effects of various classes of drugs failed to demonstrate that ACEI play any specific renoprotective role (20,30 -33).…”
Section: Renal Protectionmentioning
confidence: 99%